« Pieds Noirs Rythmes : un orchestre de détenus OAS dans le “Sing-Sing” français » - Jean-Claude Vimont (Criminocorpus)
From 1962 to 1968, several hundreds of activist members of the OAS (Organisation of the Secret Army), i.e. partisans of a French Algeria, were condemned to be incarcerated in the barracks of Thoiras, a maximum-security prison located near the citadel of Saint-Martin-de-Ré. On the premises, they benefited from a particularly favourable treatment of political detention which granted them many privileges. Several prisoners created an orchestra which they called the « Pieds Noirs Rythmes » (as « Pieds Noirs » refers to French settlers in Algeria, who had to « return » to mainland France after the 1962 Algerian independence). They gave a few concerts and played at some evening parties. It is thanks to photographies secretly taken by one the prisoners, Armand Belvisi, that this forgotten band has recently been brought back to our memories.